Studi Fenomenologis Tentang Motivasi Kelompok Resiko Tinggi Hiv/Aids Dalam Melakukan Vct (Voluntary Counselling And Testing) Di Puskesmas Duren Bandungan - Wahyuningtyas, Eka Sakti; Purwaningsih, Heny (Journal of Holistic Nursing Science, 2014)
The presence of the Group expected VCT programs at high risk have a motivation to checked themselves in VCT clinic to be able to know as early as possible the condition of his health, so that further action can be immediately given. In addition VCT programs is the entrance to the advanced services namely care support and treatment so it is very important for accessible professionally. The purpose of research is to describe how the phenomenon of high risk group of motivation in conducting VCT (Voluntary Counselling and Testing) at Publich Health Care Duren, Bandungan. The method of sampling is done using a sample of snowball (snowballing sampling), non-randomized methods to obtain samples from the sample information earlier. Data collection conducted in-depth interviews with. Test validity in this study using the method of discussion groups. Based on research results, obtained that driving within factor for conducting VCT comes from the existence of a will, the desire, and awareness of self. Reason or catalyst in conducting VCT gleaned from interviews with respondents, namely to know the status of HIV/AIDS, get information about HIV/AIDS, and the prevention of HIV/AIDS. Results of the study also mentions the presence of outside influence or environment in providing motivation for doing the VCT through outreach and discussion.